Robot-Assisted Laparoscopic and Thoracoscopic Surgery: Prospective Series of 186 Pediatric Surgeries - Navarrete Arellano, Mario; Garibay González, Francisco (Frontiers in Pediatrics, 2019)
Objetive We present the applications and experience of robot-assisted laparoscopic and thoracoscopic surgery (RALTS) in pediatric surgery. Material and Methods Prospective and longitudinal study, from March 2015 to March 2018, of pediatric population, non-random sample, all treated with RALTS. Were registered: Gender, age, weight, height, diagnoses, surgical technique, time of console surgery, estimated bleeding, need for hemotransfusion, complications, conversions, postoperative hospital stay and follow-up. The Clavien-Dindo classification of complications was used. The da Vinci model Si surgical system was used (Intuitive Surgical, Inc. Sunnyvale, CA. U.S.A). We use measures of central tendency. Results In the 36-month period, we performed 186 RALTS in 147 pediatric patients and one adult, 53.23 % were male, and rest female, average age was 83 months, range 3.5 to 204 months, a patient of 63 years. The stature 116.6 cm average, range 55 to 185 cm, average weight 26.9 kg, range 5 to 102 kg, smallest patient 3.5 months, stature 55 cm and 5.5 kg of weight. We performed 38 different surgical techniques, grouped in 4 areas: urological 91, gastrointestinal and hepatobiliary (GI-HB) 84, thoracic 6 and oncological 5. The console surgery time 137.2 minutes average, range 10 to 780 minutes. The surgeon 1, performed 154 operations (82.8%) and rest the Surgeon 2. Conversion rate 3.76 %. The most performed surgeries were: pyeloplasty, fundoplication, diaphragmatic plication and benign tumors respectively by area. They were hemotransfused 4.83%, and complications occurred in 2.68 %. The average postoperative stay 2.58 days. The average follow-up 23.5 months. Results of 4 areas are analyzed in detail. Conclusion The RALTS is safe and effective in children. An enormous variety of cases can be safely performed including complex cases in small children, as hepatobiliary and thoracic surgery. There are few prospective series published of RALTS in pediatric population and most are only urological. The robotic assistance for characteristics overcomes the limitations of laparoscopy and increases the capabilities of the surgeon and can have many different procedures accomplished with excellent results. It is important to offer children the advantages and safety of minimal invasion with robotic assistance, however, in children has been slowly adopted.